THE OFFENCE - CONSTITUTIONAL CHALLENGES OR CONTROVERSIES - Pătrăuș, Mihaela Elvira (International Journal of Legal and Social Order, 2025)
The legal assessment 11 years after the entry into force of the new Criminal Code allows us to argue that the current regulation has posed important challenges for legal theorists and practitioners, with some regulations being declared unconstitutional, others being modified and supplemented to meet the demands imposed by the new realities. The outlined evolution of Romanian criminal law in the new Criminal Code from the initial moment of its adoption until this date creates the impression of a slightly cracked base for a lasting reform, even if the legislator's intention was to abandon the traditional influence and to follow a normal and natural path of assimilation of European criminal law, in order to actively contribute to the homogenization of the criminal justice system at the level of the European Union. Within the framework of this theoretical approach that we have proposed, we intend to make a brief analysis of the concept of offence, as a fundamental institution of criminal law, which polarizes all the regulations in criminal law. The current Criminal Code defines the concept of offence differently from the previous regulation, abandoning social danger as an essential feature of the offence. The new approach transposed into the provisions of art.15 of the Criminal Code, which we wish to develop, including from the perspective of comparative criminal law, is not immune to criticism, as in judicial practice situations have been identified in which the unconstitutionality of the legal text was invoked, since the content of the typical elements of a offence does not refer to the social danger of the committed act. In relation to these aspects, we propose to demonstrate that the current regulation complies with constitutional and European requirements, even if, from the perspective of the accuracy of the norm, we have objections.